\left\{ \begin{array} { l } { 6 y - 4 = 10 y - 20 n } \\ { 6 y - \frac { y } { 12 } = 3 y + 184 } \end{array} \right.
Solve for y, n
y = \frac{2208}{35} = 63\frac{3}{35} \approx 63.085714286
n = \frac{2243}{175} = 12\frac{143}{175} \approx 12.817142857
Graph
Share
Copied to clipboard
72y-y=36y+2208
Consider the second equation. Multiply both sides of the equation by 12.
72y-y-36y=2208
Subtract 36y from both sides.
36y-y=2208
Combine 72y and -36y to get 36y.
35y=2208
Combine 36y and -y to get 35y.
y=\frac{2208}{35}
Divide both sides by 35.
6\times \frac{2208}{35}-4=10\times \frac{2208}{35}-20n
Consider the first equation. Insert the known values of variables into the equation.
\frac{13248}{35}-4=10\times \frac{2208}{35}-20n
Multiply 6 and \frac{2208}{35} to get \frac{13248}{35}.
\frac{13108}{35}=10\times \frac{2208}{35}-20n
Subtract 4 from \frac{13248}{35} to get \frac{13108}{35}.
\frac{13108}{35}=\frac{4416}{7}-20n
Multiply 10 and \frac{2208}{35} to get \frac{4416}{7}.
\frac{4416}{7}-20n=\frac{13108}{35}
Swap sides so that all variable terms are on the left hand side.
-20n=\frac{13108}{35}-\frac{4416}{7}
Subtract \frac{4416}{7} from both sides.
-20n=-\frac{8972}{35}
Subtract \frac{4416}{7} from \frac{13108}{35} to get -\frac{8972}{35}.
n=\frac{-\frac{8972}{35}}{-20}
Divide both sides by -20.
n=\frac{-8972}{35\left(-20\right)}
Express \frac{-\frac{8972}{35}}{-20} as a single fraction.
n=\frac{-8972}{-700}
Multiply 35 and -20 to get -700.
n=\frac{2243}{175}
Reduce the fraction \frac{-8972}{-700} to lowest terms by extracting and canceling out -4.
y=\frac{2208}{35} n=\frac{2243}{175}
The system is now solved.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}